Competency of Barangay Tanod in Mainstreaming Peace and Order (Ascendens Asia Singapore – Union Christian College Philippines Journal of Multidisciplinary Research Abstracts, 2023)
This study aimed to evaluate the competence level of Barangay Peacekeeping Action Team (BPAT) members in Barangay Lingsat, City of San Fernando, La Union. Competency, within the context of this study, pertains to the skill set and qualities required for effective job performance. It is the ability to carry out specific tasks at a targeted proficiency level. A competent individual can respond to various situations by employing successful behaviors from past experiences. This necessitates having a repertoire of potential actions at their disposal, along with appropriate training. Competence naturally develops through accumulated experience and relevant training initiatives. The overarching aim of this research encompassed a multifaceted assessment, encompassing the level of implementation, competency, effectiveness, and the gravity of challenges faced by the Barangay Tanods in Barangay Lingsat, City of San Fernando, La Union. The chosen research method was descriptive. Data was collected using a survey questionnaire structured according to the guidelines outlined in the BPATs Manual of 2009. The data analysis relied on the calculation of weighted means, which were employed to gauge the competency level, effectiveness, and severity of issues encountered by the barangay tanods. Upon analyzing the data, several key findings emerged: • The Barangay Peacekeeping Action Team (BPAT) stood out as a remarkably effective element within the barangay's peace and order initiatives, particularly on conflict resolution, environmental preservation, law enforcement, public safety, and disaster management.  • Despite their notable effectiveness and competency, the Barangay Tanods faced challenges, such as inadequate information dissemination and insufficient fund allocation, which posed significant obstacles to their smooth operations.•  Based on these findings, several recommendations were put forth by the researchers:• Sustained Implementation: The Barangay Tanods were advised to maintain their diligent execution of duties. This would contribute to fostering a law-abiding community that respects ordinances and regulations.• Competency Continuation: It was suggested that the Barangay Tanods focus on continuous competency enhancement. This ongoing development is essential for their sustained performance and nurturing a positive community relationship.• Supporting the Justice System: A collaborative approach was proposed involving the Barangay Tanods and the barangay justice system. This synergy would reinforce peace and order and facilitate positive interactions with local barangay officials.• Training and Workshops: To ensure effective deployment, the BPAT members were recommended to undergo various training and workshops. These initiatives would equip them with comprehensive knowledge of their responsibilities.• Proposed Measures Implementation: Finally, the researchers advocated adopting measures to enhance BPAT implementation. This move would contribute to the improved and refined execution of BPAT responsibilities. In conclusion, this study not only evaluated the competency and effectiveness of the Barangay Tanods in Barangay Lingsat, City of San Fernando, La Union but also emphasized the importance of continuous improvement, collaboration, and adequate resourcing to ensure a robust peacekeeping and community safety framework.
Keywords: Competency; Peace and Order; Barangay Tanod